Development of a potentially low young's modulus (Ti-34Nb-25Zr-XFe) base alloy for orthopaedic device application - Nemavhola, Mavis Khathutshelo (Vaal University of Technology, 2019)
Elemental titanium (Ti), niobium (Nb), zirconium (Zr), and iron (Fe) powders were used to fabricate four near-β alloys with non-toxic of composition Ti-34Nb-25Zr, Ti-34Nb-25Zr-0.4Fe, Ti-34Nb-25Zr-1.2Fe, and Ti-34Nb-25Zr-2Fe (wt. %) (TNZ and TNZF) using spark plasma sintering (SPS) of nano-crystalline powders attained by high energy ball milling. The fabricated alloys were compared to Ti-34Nb-25Zr (used as a benchmark alloy in this study) and comparison was made with the commercially used Ti base alloys produced either by conventional methods or powder metallurgy. The powder mixtures were milled for 5 hours using a Simoloyer high energy ball mill with a ball to powder ratio of 10:1 and a rotational speed of 1000 rpm. This was followed by sintering the mechanically alloyed powders at 1100 ºC for 10 minutes with a pressure of 50 MPa and a heating rate of 100 ºC/min using an H-HP D25 spark plasma sintering furnace (FCT System, Germany). The powders were characterised for particle size and crystal structure using SEM and XRD. The consolidated components were characterised with regards to density, microstructure, mechanical properties. The electrochemical behaviour of the alloys was investigated using a Digi Ivy DY2300 series potentiostat. Three corrosion medium, Sodium chloride (NaCl), phosphate buffered saline solution (PBS) and Dulbecco’s modified eagle’s medium that mimic the conditions in the human body were used. Mouse myoblast cell line (C2C12) was used to investigate the biocompatibility of the sintered alloys in 1010x5 mm specimens using standard colorimetric assay MTT. Both electrochemical and biocompatibility test were conducted in triplicates and the results compared with that of the benchmark. Results of mechanical alloying of powder mixtures demonstrated an inhomogeneous structure. Milling for 5 hours resulted in agglomeration of small Fe and Zr particles. Milling for 3 hours resulted in a better distribution of elements compared to longer milling times. Therefore, sintering powders milled for 3 hours would have yielded better results. The densification results were acceptable and ranged between 97-99% of theoretical densities. Although some porosity was observed, especially on the un-etched microstructure. An insignificant decrease in density was observed when 1.2 (wt. %) Fe was added. The sintered samples had microstructures which were not homogenous. However, the addition of Fe yielded a more homogeneous microstructure compared to the one with less Fe. Therefore, TNZF with 2 (wt. %) Fe had a more homogenous microstructure. Sintering at 1100 ºC resulted in undissolved niobium and titanium which were observed in the microstructure as dark and white areas. The hardness of the TNZF alloys were comparable and lied between 373 and 432 Hv. These hardness values are higher than other similar titanium-based alloys fabricated using conventional methods. The addition of Fe to TNZ showed an insignificant decrease in hardness. The addition of Fe was found to decrease the Young’s Modulus of TNZ from 119.1 to 80 GPa with an addition of 2 wt.% Fe. However, an unacceptable reduction (230.91 to 158.2 MPa) in strength was also noticed. Pseudo passivation was observed when the alloys were immersed in 0.9 % Sodium Chloride (NaCl) which could be attributed to the inhomogeneity in the microstructure. The possibility of pitting corrosion was also observed. The alloy containing 2 Fe (wt.%) was found to be more corrosion resistant than the other alloys. The TNZF alloys exhibited better corrosion resistance in 0. 9% NaCl compared to phosphate buffered solution (PBS) and DMEM. The corrosion behaviour in PBS and DMEM cannot clearly be explained from the graphs. The morphology of the corroded samples was almost the same for all the alloys in different corrosion media. The microstructures showed pits which could have been from the pores that acted as initiation sites for pitting. In cell culture for 1 and 7 days, the cell viability for TNZF alloys was greater than that of the control group (TNZ). A significant decrease in cell viability for TNZF was observed in cell culture for 4 days. The addition of Fe on TNZ do not cause toxic effects and show good cell adhesion, indicating in-vitro cytocompatibility. The greatest cell viability of 102±3.0 % for Ti-34Nb-25Zr-2Fe. The analysis of cell morphology indicated good cell-substrate interaction. The TNZF alloys developed in this study can be suitable candidates for orthopaedic implant application due to their low Young’s modulus, corrosion resistance and superior biocompatibility. However, the strength needs significant improvement. The advantage of this biomaterial, when compared to commercial alloys, is the absence of cytotoxicity elements such as Al and V.
M. Tech. (Department of Metallurgical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Young's modulus; Alloys; Powder mixtures; Biocompatibility; Microstructures; Dissertations, Academic -- South Africa.; Elasticity.; Powder metallurgy.; Biomedical materials.; Microstructure.